2017
DOI: 10.1080/21623945.2017.1288321
|View full text |Cite
|
Sign up to set email alerts
|

The role of glucose-6-phosphate dehydrogenase in adipose tissue inflammation in obesity

Abstract: Obesity is closely associated with metabolic diseases including type 2 diabetes. One hallmark characteristics of obesity is chronic inflammation that is coordinately controlled by complex signaling networks in adipose tissues. Compelling evidence indicates that reactive oxygen species (ROS) and its related signaling pathways play crucial roles in the progression of chronic inflammation in obesity. The pentose phosphate pathway (PPP) is an anabolic pathway that utilizes the glucoses to generate molecular buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 49 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…NADPH oxidases generally act as pro-oxidant enzymes, playing a crucial role in the pathogenesis of diabetes complications and the aging process. In our study, diabetes in aged rats led to a decrease in G6PDH, 6PGDH and GST only in the liver and no other tissues studied that displayed increased or unchanged G6PDH, 6PGDH or GST, suggesting the cell type-specific roles of PPP in the regulation of ROS balance, as indicated before (Park et al , 2017 ). The decline in liver G6PDH, 6PGDH and GST may be due to excessive oxidative stress as indicated previously, showing that different types of tissue increase the utilization of G6PDH and 6PGDH under oxidative stress conditions to allow efficient regeneration of NADPH and the reduction of glutathione disulfide (GSSG) to GSH via GR, which enhances the antioxidant defense system (Bolaños and Almeida, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…NADPH oxidases generally act as pro-oxidant enzymes, playing a crucial role in the pathogenesis of diabetes complications and the aging process. In our study, diabetes in aged rats led to a decrease in G6PDH, 6PGDH and GST only in the liver and no other tissues studied that displayed increased or unchanged G6PDH, 6PGDH or GST, suggesting the cell type-specific roles of PPP in the regulation of ROS balance, as indicated before (Park et al , 2017 ). The decline in liver G6PDH, 6PGDH and GST may be due to excessive oxidative stress as indicated previously, showing that different types of tissue increase the utilization of G6PDH and 6PGDH under oxidative stress conditions to allow efficient regeneration of NADPH and the reduction of glutathione disulfide (GSSG) to GSH via GR, which enhances the antioxidant defense system (Bolaños and Almeida, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we hypothesized that SS supplementation could change lipid metabolism at the transcriptional level. Increased mRNA levels of G6pdh, a rate-limiting enzyme of the pentose phosphate pathway (PPP), are reportedly associated with adipose tissue inflammation [ 51 ]. As commonly seen in obesity, the hepatic G6pdh mRNA expression was significantly increased following the HFC diet ( Figure 9 C–F).…”
Section: Discussionmentioning
confidence: 99%
“…G6PD is a rate-limiting enzyme in the pentose phosphate pathway and is indispensable in de novo lipogenesis [24]. It has also been implicated in adipose tissue inflammation and systemic insulin resistance in obesity [27]. It was recently demonstrated that abnormal activation of G6PD increases cellular nicotinamide adenine dinucleotide phosphate (NADPH), resulting in lipid dysregulation in obesity [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of preadipocyte differentiation, fatty acids, and lipid synthesis pathways, such as oxidative phosphorylation, pentose phosphate pathway, and triacylglycerol (TAG) synthesis pathway, play essential roles [24,25,26]. In these cellular bioprocesses, adenosine triphosphate synthase peripheral stalk-membrane subunit b (ATP5F1) is important for oxidative phosphorylation [25], G6PD is essential for pentose phosphate pathway [27], and GPAM, DGAT2, DCN, and LPL are the key regulators for TAG synthesis [28,29,30]. Although it is much clearer how these genes affect adipogenesis, the interactions between these pathways and miRNA networks are largely unknown.…”
Section: Introductionmentioning
confidence: 99%